Karakteristik Kualitas Daging Sapi Peranakan Ongole yang Berasal dari Otot Longissimus Dorsi dan Gastrocnemius - Nuraini, Nuraini; Hafid, Harapin (Jurnal Ilmiah Ilmu-Ilmu Peternakan, 2006)
The  research  target  was  to  know    the  characteristic  of  beef  quality  of  Peranakan Ongole  cattle  with  meat  sample  from  Longissimus  dorsi  and  Gastrocnemius.  Data  of tenderness and characteristic of chemical composition of beef using t-Student test. Result of research indicated that the musculus Longissimus dorsi is more tender than musculus Gastrocnemius.  Fat  content  of  musculus  Longissimus dorsi  was  higher  than  that  of musculus Gastrocnemius. On the other hand, water, crude protein and mineral content of musculus Longissimus dorsi was lower than those of musculus Gastrocnemius.